2012
DOI: 10.1007/s12576-012-0235-6
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous infusion of hyperosmotic NaCl solution induces acute cor pulmonale in anesthetized rats

Abstract: Intravenous hyperosmotic NaCl infusion is an effective treatment for circulatory shock. However, a fast infusion rate (2 mL/kg at the rate of 1 mL/s) induces transient hypotension. This response has been reported to be due to decreased total peripheral resistance and/or decreased cardiac performance. Although the hypotension is transient and recovers within 2 min without detrimental consequences, it is important to understand the associated hemodynamics and mechanisms. We found that the hypotensive effect was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This is supported by previous studies that have demonstrated that the transient BP reduction, which is normally seen after rapid hypertonic NaCl infusion and was present in controls, but absent in Ext1 +/- Ext2 +/- mice, is caused by a decrease in vascular resistance [3336] This transient BP reduction could not be prevented by hexamethonium, a nicotinic cholinergic antagonist, indicating that the decrease in vascular resistance is not of higher neurological origin but is caused by local factors that influence vasodilation such as nitric oxide. [33, 34]…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous studies that have demonstrated that the transient BP reduction, which is normally seen after rapid hypertonic NaCl infusion and was present in controls, but absent in Ext1 +/- Ext2 +/- mice, is caused by a decrease in vascular resistance [3336] This transient BP reduction could not be prevented by hexamethonium, a nicotinic cholinergic antagonist, indicating that the decrease in vascular resistance is not of higher neurological origin but is caused by local factors that influence vasodilation such as nitric oxide. [33, 34]…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in arterial compliance is observed in obese subjects and animals (2,8,39,42); thus, it is possible that higher AP is required to activate the baroreceptors. Because infusion of hyperosmotic NaCl solution is known to increase plasma volume and AP (1,43), we hypothesized that sodium regulation via the baroreflex might be impaired in response to chronic hyperosmotic NaCl load in rats fed a high-fat diet. To examine this hypothesis, we conducted the following experiments in rats fed a normal-fat diet or a high-fat diet: 1) we determined mean AP, water, and sodium balance, and norepinephrine excretion in response to chronic infusion of various concentrations of NaCl via a venous catheter, 2) we determined arterial baroreflex characteristics using static openloop analysis, and 3) we determined distensibility of the common carotid artery.…”
mentioning
confidence: 99%